Pay-as-you-drive as a pricing alternative in motor insurance - Waithera, Jasmine (Strathmore University, 2021)
A Pay-As-You-Drive (PAYD) pricing method simulating the replacement of the fixed costs of vehicle ownership and operation, with variable costs. The objective was to estimate the pricin effect of each strategy and deduce 'Yhether P A YD pricing can be employed as an alternativepricing method. The pricing effect is the focus of this paper. Consumers should be able to choose among various pricing structures. With a per-unit-of-distance alternative pricing scheme, drivers would be able to save money on car insurance by driving less and might even decide that some of the extra kilometers driven are not worth the cost. The data incorporated in this study is mileage data from private passenger vehicle data in the Commonwealth of Massachusetts. The data analyses over one million data points. The results showed that the traditional Generalised Linear Model (GLM) method of pricing was still more efficient. Even so, for insurers with the largest portfolios in the market, that have considerable participation in relation to the total, the Pay-As- You-Drive pricing method can be a simple and effective alternative pricing technique. The decision as to which pricing technique to employ is thus best left to the strategy of each insurer and should be analyzed in relation to the cost of each and how much this will impact positively to the result of the portfolio.
Submitted in partial fulfillment of the requirements for the Degree of Bachelor of Business Science Actuarial at Strathmore University